Sectoral price facts in a sticky-price model - Carlos Carvalho; Jae Won Lee (Rutgers University, Department of Economics, 2011)
We develop a multi-sector sticky-price DSGE model that can endogenously deliver differential responses of prices to aggregate and sectoral shocks. Input-output production linkages induce across-sector pricing complementarities that contribute to a slow response of prices to aggregate shocks. In turn, input-market segmentation at the sectoral level induces within-sector pricing substitutability, which helps the model deliver a fast response of prices to sector-specific shocks. We estimate the model using aggregate and sectoral price and quantity data for the U.S., and find that it accounts extremely well for a range of sectoral price facts.
Keywords: E30; E31; E32; 330; heterogeneity; price stickiness; sectoral data; FAVAR; sectoral shocks